Painting Anatase (TiO2) Nanocrystals on Long Nanofibers to Prepare Photocatalysts with Large Active Surface for Dye Degradation and Organic Synthesis. Issue 8 (13th March 2013) - Zheng, Zhanfeng; Zhao, Jian; Liu, Hongwei; Liu, Jiangwen; Bo, Arixin; Zhu, Huaiyong
Abstract Anatase TiO2 nanocrystals were painted on H‐titanate nanofibers by using an aqueous solution of titanyl sulfate. The anatase nanocrystals were bonded solidly onto the titanate fibers through formation of coherent interfaces at which the oxygen atoms were shared by the nanocrystals and the fiber. This approach allowed us to create large anatase surfaces on the nanofibers, which are active in photocatalytic reactions. This method was also applied successfully to coat anatase nanocrystals on surfaces of fly ash and layered clay. The painted nanofibers exhibited a much higher catalytic activity for the photocatalytic degradation of sulforhodamine B and the selective oxidation of benzylamine to the corresponding imine (with a product selectivity >99 %) under UV irradiation than both the parent H‐titanate nanofibers and a commercial TiO2 powder, P25. We found that gold nanoparticles supported on H‐titanate nanofibers showed no catalytic activity for the reduction of nitrobenzene to azoxybenzene, whereas the gold nanoparticles supported on the painted nanofibers and P25 could efficiently reduce nitrobenzene to azoxybenzene as the sole product under visible light irradiation. These results were different from those from the reduction on the gold nanoparticles photocatalyst on ZrO2, in which the azoxybenzene was the intermediate and converted to azobenzene quickly. Evidently, the support materials significantly affect the product selectivity of the nitrobenzene reduction. Finally, the new photocatalysts could be easily dispersed into and separated from a liquid because of their fibril morphology, which is an important advantage for practical applications.